Aplikasi model binomial dalam penetuan harga opsi eropa saham pt bank negara indonesia tbk (bbni) - Muthola'ah, Rina Alifatul (Maliki Interdisciplinary Journal, 2026)
An option is a contract that grants its buyer the right to buy or sell an underlying asset at a predetermined price and time. This research focuses on determining the stock option price of PT Bank Negara Indonesia (BBNI) using the Binomial Model. This method models future stock price movements by assuming two possibilities in each periodic step: an increase or a decrease. The stock price data used is the historical data of Telkom Indonesia from August 1, 2025, to August 31, 2025. Calculation parameters such as the probability (p), up factor (u), and down factor (d) were determined based on this data. The model simulation was conducted using MATLAB software to compute the option price via the Binomial Model. The simulation results demonstrate that the calculated option price converges as the number of steps increases. This study indicates that the Binomial Model, facilitated by MATLAB, can be effectively and efficiently applied to estimate the option price of BBNI stock.